Mengambil Pelajaran Dari Peralihan Sistem Sap Fico Ke Aplikasi Odoo Pada Pt Angkasa Pura Logistik - Farhan Arwis; Firman Surya; Zalida Afni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to examine the transition from the SAP FICO system to the Odoo application at PT Angkasa Pura Logistik. The data used in this research is primary data obtained from original sources. This research focuses on PT Angkasa Pura Logistik. Data collection techniques used in-depth interviews and document reviews. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Odoo was chosen because its development costs are more affordable, it supports end-to-end business integration, and it provides real-time data that enhances efficiency, flexibility, and transparency. The implementation of Odoo is accompanied by support from the change management team, which provides basic training to users. This team also prepares the User Manual (USMAN), which serves as a guide for employees in using the Odoo application.